THE IMPORTANCE OF PRODUCTION PLANNING AND CONTROL (PCP) - Souza, Matheus; Filho, Ramilio (Revista Interface Tecnológica, 2024)
The quest to reduce costs and increase efficiency has always been at the heart of organizations in relation to the production system, but nowadays, due to the dynamics of economic scenarios, other needs have arisen and require organizations to perform better within this system. To this end, Production Planning and Control (PCP) plays a fundamental role, as it coordinates resources to meet strategic, tactical and operational production plans, reducing costs and boosting results by adapting to the needs of the production process. This article aims to address the importance of production planning and control as a tool for efficiency within production processes and organizational competitiveness, ensuring profitability and organizational economic sustainability. He concludes that Production Planning and Control is essential for the company to remain competitive in the market in which it operates and an indispensable strategic tool for the organization.